2023
DOI: 10.7759/cureus.38005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phone-Based Enhanced Adherence Counseling (EAC) Among Virally Unsuppressed Key Population (KP)

Abstract: Background: Despite the reduced human immunodeficiency virus (HIV) disease burden in Nigeria and globally, the key populations (KPs) can be disproportionately burdened with HIV infection and lower treatment coverage and outcome. A viral load (VL) test is needed to monitor the treatment outcome of KP with VL suppression of < 1000 copies/mL, demonstrating a positive treatment outcome. For unsuppressed VL, enhanced adherence counseling (EAC) may improve viral suppression in people living with HIV/KPs living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Enhanced adherence counselling (EAC), which includes assessment of baseline adherence and needs, provide adherence counselling, educational sessions, and follow-up sessions has been recommended for improvement of adherence in PLHAs on ART [ 23 , 24 ]. Indeed, studies have shown that EAC is helpful in improving adherence, optimal switching to new ART regimens, and viral load suppression in both key population and general population [ 25 , 26 ]. Authors have also recommended that interventions in India should focus on mental health issues to improve adherence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced adherence counselling (EAC), which includes assessment of baseline adherence and needs, provide adherence counselling, educational sessions, and follow-up sessions has been recommended for improvement of adherence in PLHAs on ART [ 23 , 24 ]. Indeed, studies have shown that EAC is helpful in improving adherence, optimal switching to new ART regimens, and viral load suppression in both key population and general population [ 25 , 26 ]. Authors have also recommended that interventions in India should focus on mental health issues to improve adherence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%